Nectar and flower traits of different onion male sterile lines related to pollination efficiency and seed yield of F1 hybrids - Soto Vargas, Verónica Carolina (2013)
Honey bees are the main pollinators of onion crops for seed production, but owing to low attractiveness of flowers, pollination is often inadequate. Pollination problems result in low seed yields. This problem is accentuated when male sterile lines (MSL) are used to produce hybrid onion seeds. In this study, the effect of floral attributes and nectar composition on the preference of honey bees of four MSLs and one onion open pollinated cultivar were assessed. The chemical composition of nectar was described through the analysis of sugars, trace elements, volatile organic compounds, and phenol compounds. The samples studied showed qualitative and quantitative differences in the analyzed traits of flowers and nectar among the different lines. Furthermore, field observations showed a great difference on the number of bee visits and seed yield among the onion lines analyzed. For the first time, this study demonstrates that there are marked differences in the chemical composition of nectar and floral morphology between open pollinated and MSLs and also within MSLs. In addition, these differences were correlated with the number of visits and seed yield. Therefore, it would be possible to select indirectly the most promising productive MSL using simple determinations of chemical compounds or floral morphological characters.